Saúde mental em operadores de petróleo do Rio Grande do Norte - Barbosa, Silvânia da Cruz (2008)
The importance of identifying the consequence of the hours worked on people in society has been well recognized within Organizational and Work Psychology. From this point of view, the present research had the objective of analysing the effects of work regimes on the mental health of petroleum operators of Petrobrás. The sample totaled 144 subjects, corresponding to 27% of the work population. The mental health of the participants was evaluated using the following instruments of measurement: QSG-12, Scale of self-esteem, Scale of Positive and Negative Affections and the Scale of Valuable Attributes of IMST, each representing an empirical factor used to indicate and measure the five dimensions of mental health. The subjects perceptions of their work regime and the rest of their conditions of work were evaluated using scales of descriptive attributes of IMST, by applying a semi-structured questionnaire and by use of interviews. A socio-demographic file was used to collect information related to the biographical and socio-occupational profile of the worker sample. The answers to the questionnaire were inserted into the data bank of SPSS (Statistical Package for Social Science), for statistical analysis, and the interviews were analised based on the technique of Contents Analysis recommended by Bardin (1995). The main results revealed that one third of the worker sample were tense; however, the mental health of the majority was preserved. Cluster Analysis applied to the group of seven factors which measured the five dimensions of mental health identified four profiles of psychological well-being shared between members of the sample. It was observed that the people working in the system of Continuous Shift Alternation (TIR) and in the system of Pre-advising tended to present balanced and satisfactory profiles, while the ones which worked in the Administrative Field tended to present anxious and oscillating profiles, and thus were more affected psychologically. These were also the ones that also perceived the more negative aspects of their laborious conditions (reduced chances of self-improvement, physically stressful and financial resources below expectations with which to supply family and personal necessities. In agreement with the ecological model formulated by Warr (1987), the present study concluded that the positive and negative effects on the psychological well-being tended to occur as a consequence of the perceptions the petrol operators developed to face their work conditions